Floral morphology and anatomy of Fagus grandifolia subsp. mexicana (Fagaceae), an endangered-relict tree of the Mexican montane cloud forest - Rodríguez Ramírez, Ernesto Chanes (2021)
Background: This study is the first to examine the inflorescence, and the staminate and pistillate flowers of the Mexican beech, an endangered-relict tropical montane cloud tree species. Questions: Are there morphological and anatomical differences in Mexican beech's inflorescence and flowers in comparison with other beech species worldwide? Study species: Fagus grandifolia subsp. mexicana (Martínez) A.E. Murray) Study site and dates: Five Mexican beech stands from eastern Mexico, early February to early March 2017 and 2020. Methods: 400 Mexican beech floral buds and immature pistillate and staminate flowers in anthesis were collected and processed by light microscopy analysis and the pollen by scanning electron microscopy. Results: We found floral morphology and anatomy differences of this southernmost American beech species regarding the New- and Old-World taxa. We found that the inflorescence morphology of the Mexican beech is similar to some Asian beeches such as F. hayatae subsp. pashanica, F. lucida and F. longipetiolata. Notwithstanding, the staminate and pistillate flowers' anatomy is similar to that of F. grandifolia from Canada and the United States of America, F. sylvatica from Europe and F. crenata from Japan. Conclusions: The inflorescence and floral anatomical and morphological differences can be explained by possible hybridizations. Since only the pistillate and staminate flowers of F. sylvatica and F. grandifolia have been studied in detail, morphological, molecular and ecological studies of the Asian beech species are needed to achieve a better understanding of the floral morphology and anatomical evolution of these species and their relationship with the Mexican beech.